Analyzing the impact of changes in tobacco trade barriers and cigarette taxes on developing countries : a global simulation model approach - Musona, Jackson (SLU/Dept. of Economics, 2016)
While tobacco production and exports prove to be one of the major activities by most developing countries, making tobacco a strategic crop in enhancing their economies, there has been mounting pressure worldwide through international bodies such as the World Health Organization and World Bank to reduce consumption of this crop as it is considered to have drastic health implications. Increased, integrated and harmonized action to reduce the tobacco burden is therefore key priority to improving public health and alleviating poverty. As a way to reduce tobacco imports, internal trade and consumption, a number of countries worldwide especially developed, enacted trade taxes through which tobacco is covered by high import and retailing taxes. This thesis therefore explored the impact of tobacco trade taxation, on developing countries as one of the key evidence-based tobacco control and demand reduction measures. The thesis makes use of current tobacco trade policies and stipulated tobacco import and retailing taxes; through the Global simulation Model developed by Francois & Hall (2003) to analyze the impact of such taxes on developing economies’ tobacco sectors. The simulated GSIM scenarios indicate that tobacco trade restriction changes in China have a greater impact on developing countries tobacco sectors than in other markets, with world prices in developing countries going up an average 3.8% while output goes up 1.3%, when import tariff in China is scratched off. The extended GSIM results show a negative impact of tax on developing countries while contributing positively to reducing tobacco demand and consumption. A 10% point increase in cigarette tax will reduce global tobacco output by average 0.39%. Sensitivity analysis of Armington elasticities shows short run elastic industry supply by developing countries and results are not affected by changes in elasticity values.